The idea λεκτόν in stoicism - Kucharczyk, Janusz (Folia Philosophica, 2000)
A theory of meaning plays an important role in the Stoic philosophy of language. This is because meaning, side by side with sound, representation, and extralinguistic reality is one of the basic ideas describing the relations that the linguistic sign develops. Meaning is what can be expressed with the help of language, the internal content of the linguistic signs, a certain ideal (not in the Platonic sense of the word) bodiless object which is described and revealed with the intermediary of language, but which exists, nevertheless, outside language. It corresponds to Frege's Sinn or Saussure’s category of the signified. The Stoics distinguished between the full meaning, such as the meaning of sentences, that is both of judgements and. for example, of questions, requests, or orders, on the one hand, and the incomplete meaning, such as the meaning of particular words, of predicates, or of declinable words. Formal logic is part of the theory of full meaning. This discipline makes use of many different sciences and arts which belong to linguistics, philosophy, and logic, and which comprise both a typically grammatical information and a more theoretical, philosophical and logical, competence.